Sistem Seleksi Penerimaan Siswa Baru Berdasarkan Cabang Olahraga Dengan Menggunakan Metode Promethee - Hamulian, Lagut; agustin, agustin (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2020)
Senior High School of Sports is a secondary school that aims to channel the interests and talents of students from the junior high school level (SMP) in the field of sports. In Riau itself there is only one secondary school in the field of sports, namely SMA Negeri Sports. Many students who have talent in the field of sports who have graduated from junior high school (SMP) wish to enter the Sports High School, but Sports High School has special criteria to determine which students are entitled to enter the high school. These criteria are used to determine the sport that is suitable for students based on the criteria that are fulfilled. The system is designed using the Promethe method. Promethee is a method of determining the order (priority) in Multi Criterion Decisin Making (MCDM). The Promethee method uses criteria and weights from each criterion which are then processed to determine the selection of alternative fields, the results of which are sequentially based on their priorities. The results of this study, this method can help the school select students who enter SMA Negeri of Sports in determining the sport that is suitable for these students.